Uso del cuento pictográfico en el desarrollo del lenguaje en los niños de 4 años de la unidad educativa francisco Huerta Rendón, cantón Babahoyo, 2021 - Carriel Rosado, Marcela Katherine (2021)
The problem of language development in 4-year-old children in times of pandemic has been affected by the little stimulation from teachers and parents that during the year and a half children have been receiving virtual classes, where many have been limited Resources and strategies on the part of the teacher and the little time that the classes teach have been reflected in the integral development of the child. Starting from the premise that initial education has a projection in later ages, since it enables learning for a future life. The present research is carried out in view of the concern to improve the quality of education and because children acquire knowledge in different ways, according to their needs and interests, the pictographic story has been taken into consideration as a motivating strategy to develop language . The formative potential of the pictographic story goes beyond success in learning, because stories provide culture, values, an aesthetic sense, it acts on the formation of the child's personality, it is a source of recreation and joy, it is a complete instrument for development. of communication skills. This work aims to identify the relevance of pictographic stories in the development of language in 4-year-old children, through the telling of stories to favor the participation of students in the restructuring of stories, it has a high educational impact by promoting the development of research skills in the profession and teacher performance with a proposal aimed at achieving improvements in the quality of learning